'Each in his narrow cell for ever laid': Dunedin's Southern Cemetery and its New Zealand Counterparts - Alexander Trapeznik; Austin Gee (Public History Review, 2013)
This article compares aspects of the design, layout and purpose of a range of historic New Zealand urban cemeteries with the Southern Cemetery in Dunedin. It makes use of recent research conducted for historic conservation reports which has enable detailed comparisons to be made for the first time. The Southern Cemetery survives as a representative example of a modern, urban cemetery of the mid-nineteenth century, though it is unusual in being in a comparatively unaltered state. It is shown that denominational division was a requirement from the outset in most places, contrary to the widespread assumption that it was uncommon. No major regional differences between cemeteries are to be found other than those due to the ethnic and religious pattern of settlement. The topography of cemeteries is also considered, together with their siting, plantings, specialised structures, maintenance, and their vulnerability to vandalism, ‘improvement’ or destruction.